Resilience of hop (Humulus lupulus L.) to salinity, heat and drought stresses: A mini-review - Marceddu, Roberto; Carrubba, Alessandra; Sarno, Mauro (Frontiers in Plant Science, 2022)
Over recent years, the cultivation of hops (Humulus lupulus L.) has spread widely in the Mediterranean, also affecting the southern regions of Spain and Italy with a typical semi-arid climate. Several and recent studies have investigated the responses of this species to the main abiotic stresses, which is an aspect of absolute relevance to the knowledge of the adaptive capacity of hops to the growing conditions of a new cultivation environment. Moreover, given the fact that hops’ phytochemical composition is determined primarily by genetic and environmental factors, and that the species is perennial, the lack of knowledge on the effects of abiotic stress could be reflected in subsequent years, which means multi-year economic risks. This review work therefore aims to showcase, based on an in-depth investigation of the available literature, the response of hop to the main abiotic stresses, and the effect of these on productive and qualitative crop performances. The data presented will be useful to the understanding of constraints and to the identification of useful coping strategies to the cultivation of hops in semi-arid Mediterranean environments.